A method for preparing a nano-fritted alloy
Patent Information
- Application Number
- CN202611242849.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-13
AI Technical Summary
目前工业常用耐磨部件分为高锰钢、低合金耐磨钢等纯金属耐磨件和传统陶瓷复合耐磨件,其中,纯金属耐磨件虽然韧性较好但耐磨性能和耐高温性能不足,使用寿命短,需频繁更换,导致设备停机成本高;而传统陶瓷复合耐磨件多采用微米级陶瓷颗粒通过粘接或镶嵌方式与金属基体结合,存在陶瓷颗粒易团聚、连接强度不足、易脱瓷掉瓷等问题,应用有限
本发明采用铁基合金为基体,配合具有共价键晶体结构的氮化硅/碳化硅/氮化硼核心陶瓷颗粒与纳米氧化锆辅助颗粒的复合增强体系,高温下不易发生相变或软化,保证了增强相的本征热稳定性,而纳米氧化锆在受热过程中发生相变产生体积膨胀,对基体形成压应力,补偿了陶瓷颗粒与铁基体之间热膨胀系数差异所致的拉应力,同时氧化锆优先与熔液中氧结合形成稳定氧化物,延缓了界面氧化剥落,从而制得的纳米熔瓷合金具有较好的耐高温性能,满足了矿山、冶金等领域的使用需求。
Smart Images

Figure CN122898787A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic alloy preparation technology, and specifically to a method for preparing a nano-ceramic alloy. Background Technology
[0002] Carbon steel and low-alloy steel workpieces are widely used in mining, metallurgy, ports, power, and building materials industries due to their low cost and excellent machinability. However, these wear-resistant parts in industrial settings are subjected to long-term material impact, severe friction, and high-temperature environments, placing stringent requirements on the wear resistance, impact toughness, and high-temperature resistance of the materials. Currently, commonly used industrial wear-resistant parts are divided into pure metal wear-resistant parts such as high-manganese steel and low-alloy wear-resistant steel, and traditional ceramic composite wear-resistant parts. Among them, pure metal wear-resistant parts, although having good toughness, have insufficient wear resistance and high-temperature resistance, resulting in a short service life and frequent replacement, leading to high equipment downtime costs. Traditional ceramic composite wear-resistant parts mostly use micron-sized ceramic particles bonded to the metal matrix through adhesion or embedding, which has problems such as easy agglomeration of ceramic particles, insufficient bonding strength, and easy detachment of ceramic particles, limiting their application.
[0003] To address this, Chinese patent CN110004316A discloses a method for preparing in-situ nano-ceramic particle-reinforced aluminum matrix composites. While this method solves the problem of poor wettability between ceramic particles and molten aluminum through in-situ self-generation, the matrix is an aluminum-based alloy. Its strength, high-temperature resistance, and wear resistance still cannot meet the performance requirements of iron-based wear-resistant parts in heavy-duty, high-temperature environments such as mining and metallurgy. Furthermore, vacuum rapid quenching technology has high equipment requirements, making it difficult to achieve integrated molding of large-size wear-resistant parts, thus limiting large-scale production capacity. Chinese patent CN111961904A discloses a method for preparing nano-ceramic phase-reinforced metal matrix composites, using micron-sized ceramic particles crushed by ball milling and then molded using 3D printing technology. However, 3D printing technology suffers from low efficiency and high cost in layer-by-layer molding, making it difficult to meet the mass production needs of large wear-resistant castings such as crusher liners. Moreover, achieving nano-sized micron-sized ceramic particles through ball milling involves a long process route and limited crushing efficiency, making precise control of particle size distribution difficult, severely restricting the industrial application of nano-ceramic-reinforced metal matrix composite technology in the field of iron-based wear-resistant parts. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention prepares a nano-fused ceramic alloy with good interfacial bonding strength, wear resistance, and high-temperature resistance, making it suitable for wear-resistant parts in mining, metallurgy, and other fields.
[0005] To achieve the above objectives, the present invention provides the following technical solution to address the technical problem: In a first aspect, the present invention provides a method for fabricating a nano-fused-to-ceramic alloy, comprising the following steps: S1. Mix the core particles and auxiliary particles at a mass ratio of 8:2 to 7:3 to obtain composite ceramic particles. Then mix the nano-titanium powder and silane coupling agent at a mass ratio of (1.5 to 2.5):1 to obtain a surface modifier. Preferably, the core particles are one or more of silicon nitride, silicon carbide, and boron nitride, with a particle size of 50-200 nm; the auxiliary particles are nano-zirconia with a particle size of 30-80 nm; the core particles and auxiliary particles are mixed and then vacuum premixed at a pressure of 0.08-0.1 MPa for 15-20 min; the alloy substrate comprises, by weight, 8-12 parts chromium, 3-5 parts nickel, 2-4 parts manganese, with the balance being iron.
[0006] Preferably, the alloy substrate also contains ≤5% by mass of qualified scrap steel conforming to GB / T 4223-2017 standard.
[0007] S2. The ceramic particles are dried by gradient heating, and then surface modification and activation treatment is carried out by ball milling and ultrasonic dispersion synergistic process to obtain pretreated ceramic particles.
[0008] Preferably, in step S2, the gradient heating and drying process is as follows: holding at 80℃ for 1 hour, then increasing to 100-120℃ at 20℃ / h and holding for 1-2 hours to ensure the moisture content is <0.5%; the ball milling and ultrasonic dispersion synergistic process is as follows: adding the dried ceramic particles and surface modifier to anhydrous ethanol for wet ball milling for 2-3 hours, and then ultrasonically dispersing at 20-30kHz and 200-300W for 15-20 minutes.
[0009] Preferably, in step S2, if the moisture content after drying is ≥0.5%, the drying time is extended by 0.5 to 1 hour or the temperature is raised to 125 to 130°C; if there are agglomerated particles with a particle size >500 nm after ball milling, anhydrous ethanol is added and ball milling is continued for 30 minutes, and ultrasonic-assisted dispersion is added.
[0010] S3. The alloy substrate is subjected to medium-frequency induction melting under a protective gas. After heating to the melting temperature, it is held at the temperature. Dynamic temperature control and online deoxidation are combined. After the composition is adjusted to meet the requirements, the alloy melt is obtained.
[0011] Preferably, in step S3, the dynamic temperature control is: increasing the temperature from 50 to 80°C / min to 1500 to 1600°C, and adjusting the power in real time according to the fluctuation of the melt temperature; the online deoxidation is: adding a deoxidizer when the content of oxide slag detected by infrared is ≥0.3%, and removing the residue by electromagnetic adsorption after deoxidation.
[0012] Preferably, in step S3, the composition adjustment is combined with the element burn-off rate supplementation, with Cr burn-off rate of 1% to 20% and Ni burn-off rate of 0% to 5%, and the composition deviation ≤ ±0.3%; if the deviation exceeds the tolerance, the heat preservation is extended for 5 to 10 minutes and protective gas is introduced for stirring.
[0013] S4. Add the pretreated ceramic particles to the alloy melt, and use segmented stirring and ultrasonic-assisted dispersion process to uniformly disperse the ceramic particles. Add a fine-refining agent and continue stirring to obtain a fusion system.
[0014] Preferably, in step S4, the segmented stirring is performed as follows: 300-350 r / min for the first 10 minutes, 400-450 r / min for the middle 10 minutes, and 350-400 r / min for the last 10 minutes; ultrasonic-assisted dispersion is performed simultaneously with a power of 200-300 W; the micronizer is titanium powder, added at 0.5%-1.0% of the alloy melt mass, and its surface is pretreated with a silane coupling agent.
[0015] S5. The fusion system is gravity-cast into a mold with a temperature change buffer layer and then cooled in stages to obtain a blank.
[0016] Preferably, in step S5, the temperature change buffer layer is a ceramic fiber buffer layer with a thickness of 5-10 mm, which is wrapped around the inner wall of the mold; the mold is preheated to 200-300℃ with a heating rate of 50℃ / h; the casting speed is 5-8 kg / min; the segmented cooling is: natural cooling above 200℃ and air cooling below 200℃.
[0017] S6. The blank is subjected to segmented heat preservation annealing stress relief treatment, and after passing ultrasonic flaw detection, it is machined to obtain the finished nano-fused ceramic alloy.
[0018] Preferably, in step S6, the segmented heat preservation annealing is as follows: the first stage is held at 800-850℃ for 1-1.5h, the second stage is held at 850-900℃ for 1-1.5h, and then cooled to room temperature at 50℃ / h; the secondary annealing temperature is 750-800℃ and held for 1.5-2h, which is only for blanks with stress >150MPa; ultrasonic testing shows that the diameter of the defect is ≤0.5mm to be qualified.
[0019] Preferably, it also includes S7 finished product inspection and optimization: the hardness, impact toughness, wear resistance and high temperature resistance of the machined finished product are tested. If the performance does not meet the standard, low temperature tempering at 200-250℃ for 30-60min is used, combined with plasma spraying for 50-100μm surface strengthening.
[0020] Secondly, the present invention provides a nano-fused ceramic alloy prepared by the above-described manufacturing method.
[0021] Thirdly, the present invention provides the application of the above-mentioned nano-fused ceramic alloy in the preparation of wear-resistant parts in the fields of mining, metallurgy, ports, power, building materials, and engineering machinery.
[0022] Preferably, the wear-resistant components include crusher liners, conveyor rollers, hoppers, and wear-resistant bushings.
[0023] Compared with the prior art, the present invention has the following beneficial effects: This invention uses an iron-based alloy as the matrix, combined with a composite reinforcement system of silicon nitride / silicon carbide / boron nitride core ceramic particles with covalent crystal structure and nano-zirconia auxiliary particles. This system is less prone to phase transformation or softening at high temperatures, ensuring the intrinsic thermal stability of the reinforcing phase. Meanwhile, the nano-zirconia undergoes a phase transformation during heating, resulting in volume expansion and compressive stress on the matrix. This compensates for the tensile stress caused by the difference in thermal expansion coefficients between the ceramic particles and the iron matrix. Simultaneously, the zirconia preferentially combines with oxygen in the molten metal to form stable oxides, delaying interfacial oxidation and spalling. Therefore, the resulting nano-fused-to-ceramic alloy exhibits excellent high-temperature resistance, meeting the application requirements of mining, metallurgy, and other fields.
[0024] This invention utilizes a silane coupling agent to form a chemically bonded coating layer on the surface of ceramic particles. Nano-titanium powder imparts good lattice matching between the coating layer and the iron matrix. Together, they reduce particle surface energy and improve interfacial wettability. Ball milling provides mechanical shear force to break up agglomerates, while the microjets generated by ultrasonic cavitation further disperse submicron-sized agglomerates. Segmented stirring, through a design of increasing and then decreasing rotation speed, sequentially achieves the gradient functions of particle entrainment, strong turbulent shear dispersion, and defoaming homogenization. This complements the ultrasonic action in the time domain, ensuring uniform particle distribution in the melt and thus preventing the agglomeration of nano-ceramic particles in the alloy melt. Combined with segmented stirring and ultrasonic-assisted dispersion, uniform distribution of nano-ceramic particles is achieved under gravity casting conditions.
[0025] This invention incorporates a ceramic fiber buffer layer on the inner wall of the mold. The low thermal conductivity of the ceramic fiber buffer layer acts as a thermal barrier in the early stages of casting, slowing down the cooling rate of the casting surface and smoothing the internal and external temperature gradients. This reduces solidification shrinkage stress from the source. Combined with segmented cooling, this reduces the cracking rate of the blank. Through segmented heat preservation annealing combined with selective secondary annealing, the tempering transformation of non-equilibrium structures and the homogenization and diffusion of alloying elements are achieved, ensuring that the internal stress of the blank is completely eliminated and further releasing elastic strain energy without causing grain coarsening. Attached Figure Description
[0026] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a flowchart illustrating the preparation process of the nano-fused-to-ceramic alloy of the present invention.
[0028] Figure 2 This is a SEM image of the nano-fused-to-ceramic alloy of the present invention. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Unless otherwise specified, the experimental methods used in this invention are conventional methods; unless otherwise specified, the materials and reagents used are commercially available.
[0031] The specifications of the raw materials used in this invention are shown in the table below: Table 1 Raw Material List Example 1 In this embodiment, the alloy substrate comprises 10% chromium, 4% nickel, and 3% manganese by mass percentage, with the balance being iron and unavoidable impurities.
[0032] Ceramic particle formulation (percentage of alloy substrate mass): core particles (silicon nitride) 15%, auxiliary particles (Y2O3 stabilized nano-zirconia) 5%, with a core particle to auxiliary particle mass ratio of 7.5:2.5.
[0033] Other raw material additions (percentage of alloy substrate mass): 2% surface modifier, 0.8% micronizer (titanium powder).
[0034] like Figure 1 As shown, a method for preparing a nano-fused-to-ceramic alloy specifically includes the following steps: 1. Silicon nitride and Y2O3 stabilized nano-zirconia were mixed at a mass ratio of 7.5:2.5 and placed in a vacuum premixer. The premixing pressure was 0.09 MPa and the premixing time was 18 min to obtain composite ceramic particles. Nano-titanium powder and silane coupling agent were mixed evenly at a mass ratio of 2:1 to obtain a surface modifier.
[0035] 2. Place the composite ceramic particles in a drying oven and dry them using a gradient temperature increase: maintain the temperature at 80℃ for 1 hour, then increase the temperature to 110℃ at a rate of 20℃ / h and maintain it for 2 hours. The moisture content is measured to be 0.3%. Add the dried ceramic particles and surface modifier to anhydrous ethanol and wet ball mill them for 2.5 hours using zirconia balls as grinding balls at a ball-to-material ratio of 5:1 and a rotation speed of 350 r / min. Then, introduce 25 kHz ultrasonic dispersion for 18 minutes with an ultrasonic power of 250 W. After filtration and drying, the pretreated ceramic particles are obtained.
[0036] 3. After mixing iron, chromium, nickel, and manganese according to the formula, place them in a medium-frequency induction furnace. Under the protection of high-purity nitrogen, heat to 1550℃ at a rate of 65℃ / min to completely melt the alloy substrate. Hold at 1550℃ for 6 minutes. During the holding period, adjust the power of the medium-frequency induction furnace in real time according to the temperature fluctuation of the melt, controlling the temperature deviation within ±5℃. During the smelting process, use infrared thermal imaging to monitor the surface of the melt online. The infrared image shows that no obvious slag layer accumulation is seen on the surface of the melt, indicating that the oxide slag content has not reached the threshold for treatment (<0.3%). Therefore, no deoxidizer is added, and only sporadic floating slag is removed by electromagnetic adsorption. Hold for 6 minutes. After completion, heating was stopped and the molten liquid was allowed to cool naturally to 1360℃. At this temperature, a sample was taken for pre-furnace composition analysis (approximately 50g sample, with Cr, Ni, Mn and other element contents detected by spectrometry). The sample was taken again after a 5-minute interval, for a total of 2 samples, and the average value was used as the basis for composition adjustment. Based on a Cr burn-off rate of 10% and a Ni burn-off rate of 3%, ferrochrome and electrolytic nickel were precisely added. After addition, the temperature was maintained for another 5 minutes while nitrogen was introduced and stirred. The composition was then sampled again and re-tested, and the composition deviation was adjusted to ±0.2%. After the composition was qualified, the temperature was raised to 1520℃ and held for 6 minutes to obtain the alloy molten liquid.
[0037] 4. Allow the molten alloy to cool naturally to 1450–1480℃. Add pretreated ceramic particles to the molten alloy at a rate of 0.8 kg / min (20% of the molten alloy mass). During the addition process, maintain the temperature within the 1450–1480℃ range by adjusting the power of the medium-frequency induction furnace. Use segmented stirring: 350 r / min and 250 W ultrasonic power for the first 10 minutes, 420 r / min and 280 W ultrasonic power for the middle 10 minutes, and 380 r / min and 260 W ultrasonic power for the last 10 minutes. Add micronized titanium powder (2–3 μm particle size, 0.8% addition, surface soaked in silane coupling agent for 12 minutes and dried before use), and continue stirring for 12 minutes. After stirring, take samples from the upper, middle, and lower parts of the fused system and observe the uniformity of ceramic particle distribution using metallographic methods. After confirming no obvious agglomeration, reheat the fused system to 1520℃ and proceed to the next casting step.
[0038] 5. The reheated fusion system is gravity-cast into a cast iron mold wrapped with an 8mm thick ceramic fiber buffer layer. The mold is preheated to 250℃, the heating rate is 50℃ / h, and the casting speed is 7kg / min. Segmented cooling is adopted: natural cooling above 200℃, air cooling below 200℃, and the blank is obtained after cooling to room temperature.
[0039] 6. Perform segmented heat preservation annealing on the blank. The first stage involves holding at 820℃ for 1.2 hours, followed by a second stage at 870℃ for 1.2 hours, then cooling to room temperature at a rate of 50℃ / h. A stress tester is used to measure the stress value, which is 120 MPa, eliminating the need for secondary annealing. After annealing, ultrasonic testing is performed, and the defect diameter is found to be <0.5 mm, yielding the finished nano-fused-to-ceramic alloy. Figure 2 As shown, there are no obvious cracks or pores at the interface, the bonding is good, and the surface structure is fine, indicating that the solidification and cooling rate is relatively fast.
[0040] Example 2 In this embodiment, the alloy substrate comprises 11% chromium, 3.5% nickel, and 2.5% manganese by mass percentage, with the balance being iron and unavoidable impurities.
[0041] Ceramic particle formulation (percentage of alloy substrate mass): core particles (silicon carbide to boron nitride mass ratio 1:1) 16%, auxiliary particles (Y2O3 stabilized nano-zirconia) 4%, core particles to auxiliary particles mass ratio is 8:2.
[0042] Other raw material additions (percentage of alloy substrate mass): 2% surface modifier, 0.6% micronizer.
[0043] A method for preparing a nano-fused-to-ceramic alloy specifically includes the following steps: 1. Mix the core particles and auxiliary particles at a mass ratio of 8:2, and premix them under vacuum at a pressure of 0.08 MPa for 20 minutes; the surface modifier is prepared in the same way as in Example 1.
[0044] 2. Keep at 80℃ for 1 hour, then increase to 120℃ at 20℃ / h and keep at 1.5 hours. The moisture content is measured to be 0.4%. The dried ceramic particles and surface modifier are added to anhydrous ethanol and wet ball milled for 3 hours at a ball-to-material ratio of 5:1 and a rotation speed of 350 r / min. Then, 20 kHz ultrasonic dispersion is introduced for 20 minutes at a power of 200 W. Filter and dry.
[0045] 3. After the alloy substrate is prepared, it is placed in a medium-frequency induction furnace and heated to 1520℃ at a rate of 60℃ / min under high-purity nitrogen protection to completely melt the alloy substrate. It is then held at 1520℃ for 5 minutes, with the power adjusted in real time according to the temperature fluctuations of the melt to control the temperature deviation within ±5℃. Infrared thermal imaging monitoring shows localized slag accumulation on the surface of the melt, with an oxide slag content >0.3%. 0.4% aluminum powder deoxidizer is added, and the residue is removed by electromagnetic adsorption after deoxidation. After the holding period, heating is stopped, allowing the melt to self-heat. The temperature was then lowered to 1340℃, and samples were taken at this temperature for pre-furnace composition analysis (approximately 50g of sample was taken and detected using spectroscopic methods). Samples were taken again after a 5-minute interval, and the analysis was repeated twice. The average value was used as the basis for composition adjustment. Cr burn-off rate of 15% and Ni burn-off rate of 2% were precisely added. After the addition, the temperature was maintained for another 5 minutes while nitrogen was introduced and the mixture was stirred. Samples were taken again for composition analysis, and the composition deviation was adjusted to ±0.2%. After the composition was deemed acceptable, the temperature was raised to 1500℃ and maintained for 5 minutes to obtain the alloy melt.
[0046] 4. Allow the alloy melt to cool naturally to 1420–1460℃. Add the pretreated ceramic particles to the alloy melt at a rate of 0.6 kg / min, which is 20% of the alloy melt mass. Stir in stages: for the first 10 minutes, the speed is 320 r / min and the power is 220 W; for the middle 10 minutes, the speed is 430 r / min and the power is 260 W; for the last 10 minutes, the speed is 370 r / min and the power is 240 W. Add the micronizer titanium powder (0.6% added, the surface is soaked in silane coupling agent for 10 minutes and dried), and continue stirring for 15 minutes to obtain the fusion system.
[0047] 5. The fusion system is gravity-cast into a cast iron mold with a 6mm thick ceramic fiber buffer layer. The mold is preheated to 220°C at a heating rate of 50°C / h and a casting speed of 6kg / min. The segmented cooling is the same as in Example 1. After cooling to room temperature, a blank is obtained.
[0048] 6. Segmented heat preservation annealing The first stage involves holding at 810℃ for 1.3 hours, followed by a second stage at 860℃ for 1.3 hours, and then cooling to room temperature at a rate of 50℃ / h. The stress test value is 140MPa, eliminating the need for secondary annealing. After passing ultrasonic flaw detection, the finished nano-fused ceramic alloy is obtained.
[0049] Example 3 In this embodiment, the alloy substrate comprises, by mass percentage, 9% chromium, 4.5% nickel, and 3.5% manganese, with the balance being iron and unavoidable impurities.
[0050] Ceramic particle formulation (percentage of alloy substrate mass): core particles (silicon nitride, silicon carbide and boron nitride in a mass ratio of 2:1:1) 14%, auxiliary particles (Y2O3 stabilized nano-zirconia) 6%, with a core particle to auxiliary particle mass ratio of 7:3.
[0051] Other raw material additions (percentage of alloy substrate mass): 2% surface modifier, 0.9% micronizer.
[0052] A method for preparing a nano-fused-to-ceramic alloy specifically includes the following steps: 1. Mix the core particles and auxiliary particles at a mass ratio of 7:3, and premix them under vacuum at a pressure of 0.1 MPa for 15 minutes; the surface modifier is prepared in the same way as in Example 1.
[0053] 2. Keep at 80℃ for 1 hour, then increase to 100℃ at 20℃ / h and keep at 100℃ for 2 hours. The moisture content is measured to be 0.3%. The dried ceramic particles and surface modifier are added to anhydrous ethanol and wet ball milled for 2 hours (ball-to-material ratio 5:1, speed 400r / min). Then, 30kHz ultrasonic dispersion is introduced for 15 minutes at a power of 300W. Filter and dry.
[0054] 3. After the alloy substrate is prepared, it is placed in a medium-frequency induction furnace and heated to 1580℃ at 70℃ / min under the protection of high-purity nitrogen to completely melt the alloy substrate. It is then held at 1580℃ for 4 minutes, with the power adjusted in real time according to the temperature fluctuations of the melt to control the temperature deviation within ±5℃. Infrared thermal imaging monitoring showed no obvious slag accumulation on the surface of the melt, indicating that the oxide slag content was <0.3%, which did not meet the treatment threshold. After the holding period, heating was stopped, and the melt was allowed to cool naturally to 1380℃. At this temperature, a sample was taken for pre-furnace composition analysis (approximately 50g sample, detected using spectroscopic methods). The sample was resampled and retested after a 5-minute interval, for a total of two samplings. The average value was used as the basis for composition adjustment. Precise addition was made based on the Cr burn-off rate of 8% and the Ni burn-off rate of 1%. After addition, the temperature was held for another 5 minutes with nitrogen stirring, and the composition was resampled and retested to adjust the composition deviation to ±0.1%. After the composition was deemed acceptable, the temperature was raised to 1560℃ and held for 4 minutes to obtain the alloy melt.
[0055] 4. Allow the alloy melt to cool naturally to 1480–1500℃. Add the pretreated ceramic particles to the alloy melt at a rate of 1.0 kg / min, which is 20% of the alloy melt mass. Stir in stages: for the first 10 minutes, the speed is 380 r / min and the power is 280 W; for the middle 10 minutes, the speed is 450 r / min and the power is 300 W; for the last 10 minutes, the speed is 400 r / min and the power is 280 W. Add the micronizer titanium powder (0.9% added, the surface is soaked in silane coupling agent for 15 minutes and dried), and continue stirring for 10 minutes to obtain the fused system.
[0056] 5. The fusion system is gravity-cast into a cast iron mold with a 10mm thick ceramic fiber buffer layer. The mold is preheated to 280℃, the heating rate is 50℃ / h, and the casting speed is 8kg / min. The segmented cooling is the same as in Example 1. After cooling to room temperature, a blank is obtained.
[0057] 6. Segmented heat preservation annealing The first stage involves holding at 840℃ for 1.1 hours, followed by a second stage at 880℃ for 1.1 hours, and then cooling to room temperature at a rate of 50℃ / h. The stress test value is 110MPa, eliminating the need for secondary annealing. After passing ultrasonic flaw detection, the finished nano-fused ceramic alloy is obtained.
[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not add auxiliary particles (nano-zirconia), but only adds 20% core particles (silicon nitride), while everything else is the same.
[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step 2, the ceramic particles in Comparative Example 2 are only subjected to gradient heating and drying, without adding surface modifiers, and without ball milling and ultrasonic dispersion synergistic modification and activation treatment. The dried ceramic particles are directly used in step 4, and everything else is the same.
[0060] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step 4 of Comparative Example 3, segmented stirring is not used, but continuous stirring at a constant speed of 380 r / min for 30 min is used. Everything else is the same.
[0061] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the inner wall of the mold in step 5 of Comparative Example 4 is not covered with a ceramic fiber buffer layer, but all other aspects are the same.
[0062] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in step 5 of Comparative Example 5, after casting, segmented cooling is not used, and the blank is directly water-cooled to room temperature. Everything else is the same.
[0063] Test Example 1 Tensile strength and impact toughness test Instruments: Universal testing machine; pendulum impact testing machine; Brinell hardness tester.
[0064] Samples to be tested: Nano-fused ceramic alloy blanks prepared in Examples 1-3, Comparative Examples 1, 2, and 3 were machined into standard samples.
[0065] Experimental methods (1) Tensile strength test: According to GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test method at room temperature", the specimen was processed into a cylinder with a diameter of 25 mm and subjected to tensile testing on a universal testing machine with a loading rate of 1 mm / min. The fracture load was recorded and the tensile strength was calculated. The test results can indirectly reflect the interfacial bonding quality between ceramic particles and iron matrix. Under the premise that the type, content and distribution uniformity of ceramic particles are the same, the higher the tensile strength, the higher the interfacial load transfer efficiency and the stronger the interfacial bonding.
[0066] (2) Impact toughness test: According to GB / T 229-2020 "Charpy pendulum impact test method for metallic materials", the sample was processed into a standard Charpy V-notch sample of 55mm×10mm×10mm and tested on a pendulum impact testing machine at a test temperature of 25±2℃. The impact absorbed energy was recorded.
[0067] (3) Brinell hardness test: In accordance with GB / T 231.1-2018 "Metallic materials Brinell hardness test - Part 1: Test method", a 10mm diameter cemented carbide ball was used, the test force was 3000kgf, the holding time was 10s, and the hardness value was calculated after measuring the indentation diameter.
[0068] Table 2. Test results of tensile strength and impact toughness of different alloys As shown in Table 2, the tensile strength of Examples 1 to 3 is ≥451 MPa, and the impact toughness is ≥177 J·cm. -2 All samples had a Brinell hardness ≥502HBW. Comparative Example 1, without the addition of nano-zirconia auxiliary particles, showed a significant decrease in both tensile strength and impact toughness; Comparative Example 2, without surface modification and activation treatment of the ceramic particles, showed a significant decrease in interfacial bonding strength and impact toughness.
[0069] Test Example 2 Abrasion resistance test 1. Experimental Materials The reference material was a conventional pure metal wear-resistant part (high manganese steel ZGMn13, water-toughened), which was processed into standard specimens of the same size.
[0070] Instruments: Universal friction and wear testing machine; electronic balance (accuracy 0.1 mg).
[0071] Samples to be tested: Nano-fused ceramic alloy blanks prepared in Examples 1-3, Comparative Examples 1, 2, and 3 were machined into standard samples (blocks of 10mm × 10mm × 30mm).
[0072] 2. Experimental Methods The test ring and test block were subjected to line contact sliding wear. The test ring was made of GCr15 bearing steel and the test block was 10mm×10mm×30mm in size.
[0073] Test parameters: load 200N, sliding speed 0.5m / s, total sliding distance 2000m. The mass of the test block was weighed using an electronic balance before and after the test (accurate to 0.1mg), and the wear loss was calculated. Each group of samples was tested 5 times, and the average value was taken.
[0074] 3. Experimental Results Table 3. Test results of wear resistance of different alloys As shown in Table 3, the wear loss of Examples 1 to 3 was 10.6 to 14.3 mg. In Comparative Example 1, no nano-zirconia auxiliary particles were added, and the wear resistance was significantly reduced. Comparative Example 2 did not undergo surface modification and activation treatment, and the wear resistance was reduced the most. Comparative Example 3 did not use segmented stirring, and the wear resistance was also lower than that of the other examples.
[0075] Test Example 3 High temperature resistance and thermal shock resistance test 1. Experimental Materials Instruments: High-temperature box-type resistance furnace; Low-temperature freezer; Magnifying glass (10x).
[0076] Samples to be tested: Nano-fused ceramic alloy blanks prepared in Examples 1-3, Comparative Examples 1, 4, and 5 were machined into standard samples (size 20mm×20mm×20mm).
[0077] 2. Experimental Methods (1) High temperature resistance test: The sample was placed in a high temperature box-type resistance furnace and heated to 980℃, 1020℃, 1060℃, 1100℃ and 1140℃ respectively at a rate of 10℃ / min. After holding at this temperature for 2 hours, the sample was removed and allowed to cool naturally to room temperature. The changes in sample size were measured, and it was observed whether softening, deformation or oxidation peeling occurred. The temperature at which the sample deformed or oxidized and peeled was recorded as the critical deformation temperature.
[0078] (2) Thermal shock resistance test: The sample was placed in a -20℃ freezer for 30 minutes and then immediately placed in a 1100℃ high-temperature furnace for 30 minutes. After that, it was taken out and allowed to cool naturally to room temperature. This is one cycle. Every 5 cycles, the sample surface was observed with a magnifying glass and the presence of cracks was recorded. The number of cycles at which cracks appeared was recorded as the limit number of cycles. Five samples were tested in each group, and the average value was taken.
[0079] 3. Experimental Results Table 4. Test results of high temperature resistance and thermal shock resistance of different alloys. Table 4 shows that the critical deformation temperatures of Examples 1-3 are all ≥1060℃. After holding at 1100℃ for 2 hours, there was no deformation or oxidation spalling, and no cracks were observed after 50 cycles of thermal shock resistance. This indicates that the nano-fused-to-ceramic alloy prepared by this invention has excellent high-temperature resistance and thermal shock resistance. Comparative Example 1, without the addition of nano-zirconia auxiliary particles, had a critical deformation temperature reduced to 980℃ and thermal shock resistance of only 16 cycles, indicating that the phase transformation toughening and compressive stress compensation effects of the zirconia auxiliary particles play a crucial role in high-temperature resistance and thermal shock resistance. Comparative Example 4, without a temperature change buffer layer, had thermal shock resistance reduced to 41 cycles, indicating that the temperature change buffer layer indirectly affects the thermal shock resistance integrity of the material by reducing the initial temperature difference between the casting and the mold and alleviating solidification shrinkage stress. Comparative Example 5, without segmented cooling, had a critical deformation temperature reduced to 1020℃ and thermal shock resistance reduced to 27 cycles, showing a decline in performance. Test Example 4 Experiment on blank cracking rate and finished product qualification rate 1. Experimental Materials Production batches: 3 batches were produced for each of Examples 1-3 and Comparative Examples 1-5, with 30 pieces in each batch, for a total of 90 blanks per group.
[0080] Instruments: Stress tester; Ultrasonic flaw detector.
[0081] Samples to be tested: blanks prepared in Examples 1-3 and Comparative Examples 1-5.
[0082] 2. Experimental Methods (1) Crack rate statistics: After the blanks are cooled to room temperature in sections, the surface is checked for cracks by visual inspection and magnification. The number of cracked blanks is recorded. Crack rate = number of cracked blanks / total number of blanks × 100%.
[0083] (2) Stress detection: The residual stress of the key parts of the blank is detected by a stress tester. Ten pieces are randomly selected from each group and the average value is taken.
[0084] (3) Finished product qualification rate statistics: After the blanks are annealed, internal defects are detected by ultrasonic flaw detector. The defect diameter is ≤0.5mm as qualified. Finished product qualification rate = number of qualified finished products / total number of finished products × 100%.
[0085] 3. Experimental Results Table 5. Experimental results of blank cracking rate and finished product qualification rate for different alloys. Table 5 shows that the cracking rate of the blanks in Examples 1-3 was 0%, the average residual stress was 108-143 MPa, and the finished product qualification rate was 94%-97%. In Comparative Example 1, without the addition of nano-zirconia auxiliary particles, the cracking rate increased to 6%, and the finished product qualification rate decreased to 81%. In Comparative Example 2, without surface modification and activation treatment of the ceramic particles, the residual stress was the highest, the cracking rate increased to 13%, and the finished product qualification rate was only 69%. In Comparative Example 3, without segmented stirring, the cracking rate was 3%, and the finished product qualification rate was 87%. In Comparative Example 4, without a temperature change buffer layer, the residual stress was the highest, and the cracking rate reached 24%. In Comparative Example 5, without segmented cooling, the cracking rate reached 17%, and the finished product qualification rate was only 77%. This indicates that the temperature change buffer layer and segmented cooling play an important role in reducing residual stress, reducing cracking, and improving the finished product qualification rate.
[0086] In summary, this invention achieves improved overall performance of nano-fused ceramic alloys without the need for complex equipment by synergistically combining composite ceramic particle systems, surface modification and activation treatment, segmented stirring and ultrasonic-assisted dispersion, temperature-changing buffer layers and segmented cooling, and segmented heat preservation annealing. This meets the high-performance requirements of wear-resistant parts in harsh working conditions such as mining and metallurgy, and has good prospects for industrial application.
[0087] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing a nano-fused-to-ceramic alloy, characterized in that, Includes the following steps: S1. The core particles and auxiliary particles are mixed at a mass ratio of 8:2 to 7:3 to obtain composite ceramic particles. After drying, a surfactant is added for surface modification and activation treatment to obtain modified composite ceramic particles. S2. Under a protective gas atmosphere, the alloy substrate is subjected to medium-frequency induction melting to obtain an alloy melt; S3. Add the modified composite ceramic particles to the alloy melt, use segmented stirring and ultrasonic-assisted dispersion to uniformly disperse the ceramic particles, add a finer agent and continue stirring to obtain the fusion system; S4. The fusion system is gravity-cast into a mold with a temperature change buffer layer and then cooled in stages to obtain a blank. S5. The blank is subjected to segmented heat preservation annealing stress relief treatment. After passing the inspection, it is machined to obtain nano-fused ceramic alloy. The alloy substrate, by weight percentage, comprises 8-12% chromium, 3-5% nickel, 2-4% manganese, with the balance being iron.
2. The method according to claim 1, characterized in that, In step S1, the core particles are one or more of silicon nitride, silicon carbide, and boron nitride, with a particle size of 50-200 nm; the auxiliary particles are nano-zirconia with a particle size of 30-80 nm; the core particles and auxiliary particles are mixed and then vacuum premixed at a pressure of 0.08-0.1 MPa for 15-20 min.
3. The method according to claim 1, characterized in that, In step S1, the surfactant is prepared by uniformly mixing nano-titanium powder and silane coupling agent at a mass ratio of (1.5~2.5):
1.
4. The method according to claim 1, characterized in that, In step S1, the surface modification and activation treatment is as follows: the dried ceramic particles and the surface modifier are added to anhydrous ethanol and wet ball-milled for 2-3 hours, and then ultrasonically dispersed at 20-30 kHz and 200-300 W for 15-20 minutes.
5. The method according to claim 1, characterized in that, In step S2, the medium-frequency induction melting is carried out at a rate of 50-80℃ / min to 1500-1600℃, and held for 5-10 minutes.
6. The method according to claim 1, characterized in that, In step S3, the amount of modified composite ceramic particles added is 20% of the mass of the alloy melt.
7. The method according to claim 1, characterized in that, In step S3, the segmented stirring is as follows: 300-350 r / min for the first 10 minutes, 400-450 r / min for the middle 10 minutes, and 350-400 r / min for the last 10 minutes; ultrasonic-assisted dispersion is carried out simultaneously with a power of 200-300 W; the micronizer is titanium powder, added at 0.5%-1.0% of the mass of the alloy melt, and the surface is pretreated with a silane coupling agent.
8. The method according to claim 1, characterized in that, In step S4, the temperature change buffer layer is a ceramic fiber buffer layer with a thickness of 5-10 mm, which is wrapped around the inner wall of the mold; the mold is preheated to 200-300℃ with a heating rate of 50℃ / h; and the casting speed is 5-8 kg / min.
9. The method according to claim 1, characterized in that, In step S5, the segmented heat preservation annealing is as follows: the first stage is held at 800-850℃ for 1-1.5h, the second stage is held at 850-900℃ for 1-1.5h, and then cooled to room temperature at 50℃ / h; the second annealing temperature is 750-800℃ and held for 1.5-2h.
10. The method according to claim 1, characterized in that, The method also includes step S6, finished product testing and optimization: the finished product is tested for performance, and if it does not meet the standard, it is tempered at a low temperature of 200-250℃ for 30-60 minutes, combined with plasma spraying to strengthen the surface to 50-100μm.
Citation Information
Patent Citations
Preparation method of in-situ nano ceramic particle enhancing aluminum-based composite material
CN110004316A
Preparation method of nano ceramic phase reinforced metal-based composite material
CN111961904A